Antidiabetic and antihyperlipidemic effects of Dillenia indica (L.) leaves extract - Sunil Kumar; Vipin Kumar; Om Prakash (Universidade de São Paulo, 2011)
The present study was carried out to evaluate antidiabetic and antihyperlipidemic effects of Dillenia indica methanolic leaves extracts in streptozotocin induced diabetic Wistar rats by administering graded oral doses (250 and 500 mg/kg body weight) for 21 days. The extract showed significant antidiabetic activity (p<0.001). Furthermore, the decreased body weight of rats was significantly improved after extract treatments. Daily oral treatment with the extract for 21 days to diabetic rats, also resulted in significant reduction in serum cholesterol, triglycerides and serum transaminase levels but HDL-cholesterol level was found to be improved (p<0.001) as compared to the diabetic control group. The extract treatment also showed to enhance serum insulin level in diabetic rats as compared to the diabetic control group. In conclusion, D. indica leaf extract might be useful for diabetes mellitus management and other abnormalities associated with this metabolic disorder. Realizou-se o presente estudo para avaliar os efeitos antidiabético e anti-hiperlipidêmico de extratos metanólicos de folhas de Dillenia indica em ratos wistar com diabetes induzido por estreptozotocina por meio da administração de doses orais (250 e 500 mg/kg de peso corporal) por 21 dias. O extrato mostrou atividade antidiabética significativa (p<0,001). Além disso, a diminuição do peso corporal dos ratos foi significativamente melhorada após o tratamento com os extratos. O tratamento com doses orais do extrato por 21 dias aos ratos diabéticos também resultou em redução significativa do colesterol, triglicerídios e níveis de transaminase séricos, mas o nível de HDL-colesterol foi melhorado (p<0,001), quando comparado ao grupo controle diabético. O tratamento com extrato também mostrou aumento do nível sérico de insulina em ratos diabéticos comparativamente ao grupo controle diabético. Em conclusão, o extrato de folha de D. indica poderia ser útil para o controle do diabetes mellitus e de outras anormalidades associadas a essa disfunção metabólica.